2020
DOI: 10.3897/zookeys.986.57119
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new Megophrys Kuhl & Van Hasselt, 1822 (Anura, Megophryidae) from Guizhou Province, China

Abstract: A new species of the genus Megophrys is described from Guizhou Province, China. Molecular phylogenetic analyses based on mitochondrial DNA indicated the new species as a clade clustered into the Megophrys clade. The new species can be distinguished from its congeners by a combination of the following characters: body size moderate (SVL 40.0–45.5 mm in males and 48.9–51.2 mm in females); vomerine teeth absent; tongue not notched behind; tympanum distinctly visible, oval; a small horn-like tubercle at the edge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Diagnosis: Based on original description ( Li et al, 2020b ): (1) adult males, SVL 40.0–45.5 mm ( n =4); adult females, SVL 48.9–51.2 mm ( n =3); (2) snout obtusely pointed, canthus rostralis well developed; tongue not notched posteriorly; (3) tympanum distinct; (4) vomerine ridges present, vomerine teeth absent; (5) dorsal skin rough; weak discontinuous X-shaped ridge on center of dorsum, discontinuous dorsolateral ridges present; flanks with large warts; ventral skin smooth; (6) outer margin of upper eyelid with small horn-like prominent tubercle; supratympanic fold distinct and narrow, curving posteroventrally to above arm; (7) two metacarpal tubercles prominent and ovoid, inner one enlarged; relative finger lengths I<II<IV<III; distinct subarticular tubercle at base of each finger; (8) hindlimbs slender, heels overlapping when hindlimbs folded; tibiotarsal articulation reaching center of eye when leg stretched forward; (9) toes with rudimentary webbing at bases and narrow lateral fringes; inner metatarsal tubercle ovoid, outer one absent; (10) dorsal surface brown; brown triangular marking between eyes, X-shaped marking on center of dorsum; dorsal limbs with dark transverse bands; ventral surface brown with white patches on belly, two parallel dark brown bands ventrolaterally; (11) brownish nuptial pads bearing black nuptial spines on dorsal bases of fingers I and II in breeding adult males; subgular vocal sac present in males.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnosis: Based on original description ( Li et al, 2020b ): (1) adult males, SVL 40.0–45.5 mm ( n =4); adult females, SVL 48.9–51.2 mm ( n =3); (2) snout obtusely pointed, canthus rostralis well developed; tongue not notched posteriorly; (3) tympanum distinct; (4) vomerine ridges present, vomerine teeth absent; (5) dorsal skin rough; weak discontinuous X-shaped ridge on center of dorsum, discontinuous dorsolateral ridges present; flanks with large warts; ventral skin smooth; (6) outer margin of upper eyelid with small horn-like prominent tubercle; supratympanic fold distinct and narrow, curving posteroventrally to above arm; (7) two metacarpal tubercles prominent and ovoid, inner one enlarged; relative finger lengths I<II<IV<III; distinct subarticular tubercle at base of each finger; (8) hindlimbs slender, heels overlapping when hindlimbs folded; tibiotarsal articulation reaching center of eye when leg stretched forward; (9) toes with rudimentary webbing at bases and narrow lateral fringes; inner metatarsal tubercle ovoid, outer one absent; (10) dorsal surface brown; brown triangular marking between eyes, X-shaped marking on center of dorsum; dorsal limbs with dark transverse bands; ventral surface brown with white patches on belly, two parallel dark brown bands ventrolaterally; (11) brownish nuptial pads bearing black nuptial spines on dorsal bases of fingers I and II in breeding adult males; subgular vocal sac present in males.…”
Section: Resultsmentioning
confidence: 99%
“…Distribution: Known only from its type locality in Anlong County at elevations of 1 400–1 600 m a.s.l. ( Li et al, 2020b ) (Supplementary Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the findings of the new species also indicated a high degree of localised diversification and micro-endemism for the species in the genus Leptobrachella because in Guizhou Province, China, the five recent-described Leptobrachella species are just known only from their type localities or nearby areas. In addition, in recent years, large number of discoveries have been made from Guizhou, dramatically raising the number of frog species known from the region ( Zhang et al 2017 ; Li et al 2018a , b , 2019a , b , 2020a , b , c ; Lyu et al 2019 ; Wang et al 2019 ; Luo et al 2020 ; Su et al 2020 ; Xu et al 2020 ; Wei et al 2020 ). This further indicated that more investigations should be conducted in Guizhou Province to define more precisely distribution area of the new species and detect more cryptic species especially in the poorly-investigated areas.…”
Section: Discussionmentioning
confidence: 99%
“…Their body mass (BM) was measured using an electronic balance, and 17 morphological indices, such as snout-vent length (SVL), head length (HDL), head width (HDW), snout length (SL), internasal distance (IND), upper eyelid width (UEW), interorbital distance (IOD), eye diameter (ED), maximal tympanum diameter (TYD), tympanum-eye distance (TEY), length of lower arm and hand (LAL), hindlimb length (HLL), thigh length (THL), tibia length (TL), maximal tibia width (TW), length of foot and tarsus (TFL), and foot length (FL), were measured using a digital caliper. Measurement standards were based on studies by Li et al (2020) and Fei et al (2005).…”
Section: Morphological Datamentioning
confidence: 99%